Mildly reduced graphene oxide-Ag nanoparticle hybrid films for surface-enhanced Raman scattering - Li, Xiaocheng (2013)
Large-area mildly reduced graphene oxide (MR-GO) monolayer films were self-assembled on SiO2/Si surfaces via an amidation reaction strategy. With the MR-GO as templates, MR-GO-Ag nanoparticle (MR-GO-Ag NP) hybrid films were synthesized by immersing the MR-GO monolayer into a silver salt solution with sodium citrate as a reducing agent under UV illumination. SEM image indicated that Ag NPs with small interparticle gap are uniformly distributed on the MR-GO monolayer. Raman spectra demonstrated that the MR-GO monolayer beneath the Ag NPs can effectively quench the fluorescence signal emitted from the Ag films and dye molecules under laser excitation, resulting in a chemical enhancement (CM). The Ag NPs with narrow gap provided numerous hot spots, which are closely related with electromagnetic mechanism (EM), and were believed to remarkably enhance the Raman signal of the molecules. Due to the co-contribution of the CM and EM effects as well as the coordination mechanism between the MR-GO and Ag NPs, the MR-GO-Ag NP hybrid films showed more excellent Raman signal enhancement performance than that of either Ag films or MR-GO monolayer alone. This will further enrich the application of surface-enhanced Raman scattering in molecule detection.